Study on LiI and KI with low melting temperature for electrolyte replenishment in molten carbonate fuel cells - Bae, Jae Kwan; Kim, Hyun-Woo; Accardo, Grazia; Kim, Ghun Sik; Ham, Hyung Chul; Jang, Seong-Cheol; Cho, Yong Soo; Yoon, Sung Pil (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Molten carbonate fuel cells (MCFCs) are regarded as the closest fuel cell to commercialization due to their high capacity and energy efficiency. However, they are operated at a high temperature (620 degrees C or higher), where liquid electrolyte loss occurs during operation; hence, their lifetime is limited. For the long-term operation of MCFCs, it is essential to develop a novel method to replenish the electrolyte during operation. However, it is very difficult to directly inject the electrolyte, (Li0.62K0.38)(2)CO3, into each unit cell of the stack unless it is supplemented through liquid or gas phase at low temperature. It was verified whether LiI and KI, which have low melting points and high vapor pressures, could replenish the lost electrolyte in MCFCs. In this study, the LiI and KI injected into the unit cell in liquid phase showed a similar tendency to the Li/K carbonate electrolyte. This is because LiI and KI react with the CO2/O-2 gases supplied to the cathode during MCFC operation to form Li/K carbonate electrolytes. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: NICKEL-ALUMINUM ALLOY; SURFACE-TENSION; PERFORMANCE; MCFC; CORROSION; SYSTEM; ISSUES; NANOPARTICLES; MECHANISM; BEHAVIOR